La cocina chilota: el genuino lugar de encuentro de una comunidad bordemarina - Sahady, Antonio; Bravo, Marcelo; Quilodrán, Carolina; Gallardo G., Felipe (Revista INVI, 2011)
La cocina chilota: el genuino lugar de encuentro de una comunidad borde marina